(untitled) (Fiep Bulletin - online, 2014)
The research verified the relation between the available material resources and the quality of the classes of School Physical Education under the learning approaches teaching, in relation to the planning and achievement of the objectives, besides investigating the satisfaction of the respective students in relation to the classes and the used materials. The professors and inserted students in 8th and 9th had been made interviews with year of basic education particular and public schools in Rio de Janeiro. The criteria of choice of the citizens of the research had been the easiness of access of the researchers, the permission of the directions of the schools for the development of the research and, in the case of the students, a minimum of 75% of frequency the classes of Physical Education. The research had as resulted the students affirming not to be satisfied with the classes had, because, mainly, the structure, to the physical space and the material resources, as well as, they had affirmed not to like material used them due to little availability and the bad quality of these, how much the professors affirm to consider the resources important to trace the objectives, for one better adequacy, as also, essential for elaboration planning. And with this, can be concluded that as much in the perception of the professors how much of the students, the material resources exert influence decisive in the quality of the classes, even so the structure and the physical space of the classes to have more citations as justification about the not satisfied of the classes of Physical Education, according to opinion of the students.